Kompetensi Pengalaman Kerja dan Disiplin dalam Meningkatkan Kinerja Karyawan Rumah Sakit yang Ada di Sukabumi - Dewi Resmanasari (Digital Economic, Management and Accounting Knowledge Development (DEMAnD), 2022)
The purpose of this research is to obtain the impact of competence; work experience; and discipline towards Employee Performance. In accordance with the purpose of the causal associative method used by researchers. The population is hospital employees in Sukabumi so that the sample is drawn using the Cohcran formula, which is 97 respondents. The researcher analyzed the research data according to the research criteria by using multivariate regression analysis. The results are both independently and simultaneously with competence; work experience; and discipline have a tremendous impact on employee performance.